2021
DOI: 10.11646/phytotaxa.521.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Prosopanche cocuccii (Hydnoraceae): a new species from Southern Brazil

Abstract: Prosopanche cocuccii is described as a new species from Southern Brazil. It resembles P. bonacinae due to the trigonous rhizome and by the general size of the flower organs. Nevertheless, P. cocuccii is distinguished by the main floral morphological characteristics used to differentiate species. In addition, the new species presents some rare characters for the genus, such as a highly branched rhizome and flowers usually grouped in fascicles. We provide a description, illustrations, field photographs, morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the following century, new species and varieties were described across Argentina and Paraguay, all of which were later synonymised under Prosopanche bonacinae and P. americana by Cocucci in 1965. Since then, five new species have been described across Central and South America: Prosopanche costaricensis (G omez & G omez-Laurito, 1981), Prosopanche caatingicola (Machado et al, 2012), Prosopanche panguanensis (Martel et al, 2018), Prosopanche demogorgoni (Funez et al, 2019) and Prosopanche cocuccii (de Carvalho et al, 2021).…”
Section: Taxonomymentioning
confidence: 99%
See 3 more Smart Citations
“…In the following century, new species and varieties were described across Argentina and Paraguay, all of which were later synonymised under Prosopanche bonacinae and P. americana by Cocucci in 1965. Since then, five new species have been described across Central and South America: Prosopanche costaricensis (G omez & G omez-Laurito, 1981), Prosopanche caatingicola (Machado et al, 2012), Prosopanche panguanensis (Martel et al, 2018), Prosopanche demogorgoni (Funez et al, 2019) and Prosopanche cocuccii (de Carvalho et al, 2021).…”
Section: Taxonomymentioning
confidence: 99%
“…The entirely holoparasitic family Hydnoraceae contains just two genera, with a disjunct distribution spanning South and Central America ( Prosopanche : seven species; de Carvalho et al, 2021) and Africa and the Arabian Peninsula ( Hydnora : eight species; Bolin et al, 2018). Both genera share the same basic body plan and holoparasitic habit but vary in certain morphological and ecological characters, including host preference.…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Hydnora and its eight known species ( Bolin et al 2018 ) are found exclusively in the Old World, in Central and South Africa and Madagascar ( Musselman and Visser 1989 ). The seven species of genus Prosopanche are found in the New World, in Central and South America ( Gómez-Pignataro and Gómez-Laurito 1981 ; Musselman and Visser 1989 ; De Carvalho et al 2021 ). Hydnora and Prosopanche have an estimated crown group age of ∼55 Ma ( Naumann et al 2013 ), but could potentially be as old as the separation of the African and South American continent.…”
Section: Introductionmentioning
confidence: 99%